Epigenetics in blood–brain barrier disruption - Ihezie, Stephanie A. (Fluids Barriers CNS, 2021)
The vessels of the central nervous system (CNS) have unique barrier properties. The endothelial cells (ECs) which comprise the CNS vessels contribute to the barrier via strong tight junctions, specific transporters, and limited endocytosis which combine to protect the brain from toxins and maintains brain homeostasis. Blood–brain barrier (BBB) leakage is a serious secondary injury in various CNS disorders like stroke, brain tumors, and neurodegenerative disorders. Currently, there are no drugs or therapeutics available to treat specifically BBB damage after a brain injury. Growing knowledge in the field of epigenetics can enhance the understanding of gene level of the BBB and has great potential for the development of novel therapeutic strategies or targets to repair a disrupted BBB. In this brief review, we summarize the epigenetic mechanisms or regulators that have a protective or disruptive role for components of BBB, along with the promising approaches to regain the integrity of BBB.